Fabry Nephropathy - Vaisbich, Maria Helena; de Andrade, Luis Gustavo Modelli [UNESP]; Silva, Cassiano Augusto Braga; Barreto, Fellype Carvalho; dos Reis, Marlene Antonia (Springer Nature, 2023)
One of the main features of Fabry disease (FD) is insidious and progressive Fabry Nephropathy. These patients should have the same general measures as all patients with proteinuric kidney disease, such as control of proteinuria and hypertension, salt restriction, and modification of lifestyle, in addition to specific therapy. Specific therapy should be individualized for each patient in a sharing decision with the patient and his family. Enzyme replacement therapy (ERT) is appropriate for all patients with FD, regardless of the type of the GLA variant. Chaperone therapy is a choice only for patients with amenable variants and should not be used in patients with eGFR < 30 mL/min/1.73m2 and/or those under 16 years old. Finally, emerging therapies are under research, including next-generation ERT (pegunigalsidase alfa, moss-derived α-galactosidase A), substrate reduction therapy (lucerastat, venglustat), mRNA therapy, and gene therapy, which may provide better control of Fabry disease in the future.
Keywords: Chronic kidney disease; Fabry disease; Nephropathy; Rare diseases